Pengembangan Bahan Ajar Mata Kuliah Konversi Energi Berbasis Teknologi: Development of Technology-Based Energy Conversion Course Teaching Materials - Rizki Wijaya; Edi Setiyo (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
This study aims to develop technology-based Energy Conversion course teaching materials using the Canva application in the form of valid and practical E-Modules. The background of this study is the limitations of conventional teaching materials that are less interactive and have not utilized technology optimally, which causes low student interest and understanding of the material. The research method used is Research and Development (R&D) with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) development model. The subjects of the study were students of Mechanical Engineering Education, Sriwijaya University, class of 2022. The validation results by material experts and media experts showed that the E-Module developed was in the "Very Valid" category, with an average score of 4.6 and 4.5, respectively. The practicality trial conducted through the One-to-One, Small Group, and Field Test stages also showed that the product is included in the "Very Practical" category, with an average score of 4.25 for the One-to-one trial, 3.83 for the Small Group trial and 4.05 after being tested on all 2022 class Palembang students (Field Test). Thus, the development of this Technology-based E-Module is declared suitable for use as an alternative teaching material that can increase the effectiveness of learning and student understanding in the Energy Conversion course